Low Velocity Impact Behaviour Of Advanced Composite Materials - Rasidin, Senawi (UTeM, 2008)
The focus of this research is to study the effect of low velocity impact on composite sandwich panel that is commonly used in aerospace industries. This research investigates the effect of damage on the sandwich panel at low velocity. The specimen used in this project is carbon fiber sandwich panel and three type of testing will be carry out including Quasi-static compression test, Drop weight impact test and surface analysis using SEM. In this study, Quasi-static compression test are carried out at different velocity ranging from 2mm/min to 5mm/min. Drop weight impact test are carried out at velocity 2, 2.4,2. 97 and 3.5m/s.From the result the velocity at 3mm/min for compression test had the biggest load that is 1.95 KN. The biggest load for drop weight test at 3.5m/s is 1.26 KN. The biggest energy also at velocity 3mm/min for compression test and the value is 3.506 J. The biggest energy for drop weight test at 3.5m/s is 19 KN. From the result load and energy are directly proportional. The load increase and the energy become more increase. Several type of damages were observed under both impact test and this include upper skin failure,skin core debonding and core crushing.